Surface Defect Formation and Passivation in Formamidinium Lead Triiodide (FAPbI(3)) Perovskite Solar Cell Absorbers - YAVUZ, İLHAN (AMER CHEMICAL SOC, 2022)
Formamidinium lead iodide based hybrid perovskite materials with improved efficiency and stability still lack well-understood surface defect formation mechanisms. Controlling the surface termination and defects has the potential to improve the performance of both conventional 3D and latterly reduced-dimensional perovskites photovoltaics. Here, we characterized the termination and all possible defect formations in FAPbI(3) surface by the first-principles calculations. We found that, among the surfaces we considered, FAI-termination exhibits the most stable surface with a high defect tolerance. The PbI2- terminated surface is also found to be relatively stable; however, certain defects, such as electron-donating FA-interstitial and Pb-interstitial defects, can create deep-level stable charge-traps, potentially limiting the optoelectronic performance. We further investigate the surface treatment on these deep defects by model small molecule additives. We found that benzene additive with delocalized electron distribution can effectively passivate the deep FA-interstitial and Pb-interstitial defects by electron donating to the surface defect through charge-transfer.
Keywords: CH3NH3PBI3 PEROVSKITE; HALIDE PEROVSKITES; INTRINSIC DEFECTS; SEMICONDUCTORS; EFFICIENCY; STATE